THEEFFECTOFINSTAGRAMUSEONRELIGIOUSBEHAVIOR - Ridwan, Ridwan; Bahri, Andini Nur (Universitas Lambung Mangkurat, 2024)
This research aims to evaluate the impact of using Instagram on the religious behavior of students at the State Islamic University of North Sumatra. This study focuses on the extent to which Instagram use influences students' religious behavior. This research uses a quantitative approach by collecting data through a questionnaire instrument. The data analysis methods used are normality test, hypothesis test, simple linear regression coefficient test and determination test, then the data is processed using the SPSS 29 application. The results of the simple linear regression test show a significance value of 0.001 with a limit value of 0.05. Because 0.001 < 0.05, this indicates that the Instagram usage variable has a significant influence on religious behavior. And the results of the determination test show that there is a relationship between the use of Instagram social media and religious behavior, namely 0.295 or 29.5%. This means that variable (X) social media Instagram influences variable (Y) religious behavior by 29.5%. The remainder, namely 60.6%, comes from factors outside the research that are not included in this research model.